Role of TGF-β1/SMAD signaling cascade in the regulation of cyclooxygenase-2 expression in human breast cancer cells - M. A. Taipov; Z. N. Nikiforova; O. M. Pavlova; I. A. Kudryavtsev; N. Ye. Arnotskaya; V. Ye. Shevchenko (Опухоли женской репродуктивной системы, 2014)
The expression of the SMAD2, SMAD4, SMAD7, and СOX-2 genes and the levels of Smad4, phosphorylated Smad2, and Smad7 proteins were analyzed in the human breast cancer (BC) cell lines MCF-7, BT-474, and ZR-75-1. The SMAD2 and SMAD4 genes were found to suppress COX-2 gene expression in the estrogen receptor-positive BC cells and to be linked to their metastatic potential. Smad4 and Smad2 apparently suppress COX-2 mRNA and protein synthesis and Smad7 is their antagonist and stimulates COX-2 formation. Smad2, Smad4, Smad7 proteins may be regarded as new potential targets for targeted BC therapy.